2022
DOI: 10.4067/s0718-221x2023000100406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave treatment on drying and water impregnability of Pinus pinaster and Eucalyptus globulus

Abstract: Wood is a material that has been used by humankind for a long time. However, wood researchers and industry have always been concerned about the issues during wood drying and the permeability problems of certain species. In this sense, microwave technology has been applied for wood drying and improving permeability. This paper investigates the microwave drying of two Portuguese wood species, Pinus pinaster sap and heartwood, and Eucalyptus globulus heartwood using small clear specimens. The samples were grouped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Torgovnikov and Vinden [12] explained that under the same level of MW applied energy, for instance, to achieve a moderate degree of modification, samples containing heartwood lost more of their strength when compared to samples with only sapwood, therefore resulting in a minor modification of MOR. Furthermore, drying wood samples with only sapwood and only heartwood under the same MW parameters, Mascarenhas et al [16] showed that small clear wood specimens of Portuguese maritime pine (Pinus pinaster) containing only heartwood had a significant improvement in water uptake when compared to the samples containing only sapwood, i.e., to cause a significant improvement in water uptake it would be necessary to supply the sapwood sample with more MW energy. Therefore, based on these analyses, the density of the wood element was, in fact, a significant parameter (that influences) the variations in the MOR values after MW treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Torgovnikov and Vinden [12] explained that under the same level of MW applied energy, for instance, to achieve a moderate degree of modification, samples containing heartwood lost more of their strength when compared to samples with only sapwood, therefore resulting in a minor modification of MOR. Furthermore, drying wood samples with only sapwood and only heartwood under the same MW parameters, Mascarenhas et al [16] showed that small clear wood specimens of Portuguese maritime pine (Pinus pinaster) containing only heartwood had a significant improvement in water uptake when compared to the samples containing only sapwood, i.e., to cause a significant improvement in water uptake it would be necessary to supply the sapwood sample with more MW energy. Therefore, based on these analyses, the density of the wood element was, in fact, a significant parameter (that influences) the variations in the MOR values after MW treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Eucalypt, for instance, is a wood species with low permeability, which might be challenging to be dried and impregnated with preservative chemicals [13]. The water uptake capability of small clear samples of Portuguese Eucalyptus globulus L. made only of heartwood enhanced by around 27% after MW drying [16]. Applying highintensity MW treatment, the retention of acid copper chromate of MW-treated samples of Eucalyptus tereticornis jumped from 2.03 kg/m 3 to 9.72 kg/m 3 , a rise of more than 375% [17].…”
Section: Introductionmentioning
confidence: 99%
“…The seven samples of each sub-group were placed together in the MW to be dried simultaneously, and they were dried until they achieved an average of 12% ± 2% final moisture content. The drying program used in this work was based on previous tests and also followed what Mascarenhas et al [30] adopted in their work, with 30 s inside the MW oven (wood samples continuously exposed to MW), followed by a 30 s cooling interval (Figure 3). The MW applied energy intensity, E, was calculated using Equation (1) [11]: The drying program used in this work was based on previous tests and also followed what Mascarenhas et al [30] adopted in their work, with 30 s inside the MW oven (wood samples continuously exposed to MW), followed by a 30 s cooling interval (Figure 3).…”
Section: Microwave Dryingmentioning
confidence: 99%
“…Wood modification processes are technologies employed to modify the properties of the wood to mitigate or improve its various drawbacks, aiming, for example, to improve its mechanical properties, enhance permeability, increase biological durability, and others (Hill 2006). The microwave (MW) drying or treatment is an emerging technology capable of improving wood treatability (Torgovnikov and Vinden 2009;Mascarenhas et al 2021Mascarenhas et al , 2023aWeng et al 2021;Kol and Çayır 2022). Several authors have pointed out that MW technology can offer substantial savings in material and energy efficiency, then improve the environmental and economic performance of the wood and timber industry (Leiker and Adamska 2004;Torgovnikov and Vinden 2010;Wang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The MW device emits electromagnetic radiation that interacts with water; the molecules begin to agitate rapidly, generating increased temperature and, in turn, releasing water vapor at high temperatures (Oloyede and Groombridge 2000;Torgovnikov and Vinden 2009). This causes different wood cells and tissues to rupture, which leads to an expansion in pores and the emergence of new ones, resulting in the creation of new pathways through which water and vapor will come out of the wood (Mascarenhas et al 2021(Mascarenhas et al , 2023aTorgovnikov and Vinden 2010). Given this, there is a growth in wood porosity and permeability, which are directly linked to an increase in the capacity of wood elements to be penetrated with preservative products (Hansmann et al 2002;Hess et al 2021;Mascarenhas et al 2021).…”
Section: Introductionmentioning
confidence: 99%